Research in veterinary sciences in Kazakhstan (2018–2023): developments, gaps and opportunities - Yessembekova, Gulzhan N.; Kurishbayev, Akhylbek K.; Abdrakhmanova, Aruzhan S.; Alikhanov, Kuantar D.; Abenova, Asem Dj.; Perez, Andres M.; Abdrakhmanov, Sarsenbay K. (Frontiers in Veterinary Science, 2025)
Ensuring the welfare of livestock farms, safety of livestock products, control of epizootic situation in Kazakhstan depend on the development of scientific and technical progress. In response to this situation, in order to support the achievement of the strategic development goal, an order for the development of higher education and science in the Republic of Kazakhstan has been implemented with the aim of gradually increasing investment in scientific research to 1% of the country’s gross domestic product (GDP). Our assessment of the scientific output of veterinary sciences in Kazakhstan over the five-year period 2018–2023 demonstrated progress. The total investment in veterinary science has increased to 14 billion KZT, i.e., from 2018, the funding of projects has become annual, previously it was once every 3 years. The consequence of this transformation was a 5-fold increase in the number of published articles for example, in 2022–2023 their number reached 50 compared to 2018–2019, where the number was barely 10. Despite the positive trend in veterinary science in recent years there are still gaps in the form of inadequate funding (only 20 funded projects per year with an average allocation of <200,000 USD per project), the productivity of the scientific community has been lower than expected: 91 peer-reviewed publications were published in first quartile journals over 5 years, which is an average of one publication in first quartile journals per year for every 32 PhD researchers (with a total of 584 PhDs), concentration of science only in large cities of Kazakhstan (Astana, Almaty), scientific developments of scientists are not commercialized and have no feedback with production. Thus, there is a need to continue to improve the effectiveness of veterinary research in combination with education and retraining, as well as increasing the participation of underserved regions and communities in the country.